Chronic pudendal neuromodulation using an implantable microstimulator improves voiding function in diabetic rats. (17th May 2016) - Hsieh, Tsung-Hsun; Lin, Yin-Tsong; Chen, Shih-Ching; Peng, Chih-Wei
Abtract: Objective. Few studies have investigated the feasibility of using chronic pudendal neuromodulation for improving voiding function in patients with diabetes who are also experiencing urinary retention. The present study investigated the effects of chronic electrical stimulation (ES) of the sensory branch of the pudendal nerve on voiding function in diabetic rats. Approach. A custom-made implantable microstimulation system was designed and manufactured for chronic implantation in normal control (NC) and diabetic rats. After three or six weeks of pudendal neuromodulation, the intravesical pressure, external urethral sphincter electromyograms (EUS-EMGs), and urine flow rate (UFR) of all rats were simultaneously recorded to assess the effects of chronic pudendal ES on voiding function. Morphological changes in pudendal axons were assessed through hematoxylin and eosin (H&E) staining. Results. Abnormal cystometric measurements, including an increased volume threshold, contraction amplitude, and residual volume (RV) as well as a decreased burst period (BP) indicated voiding dysfunction in the diabetic rats with sham ES for three or six weeks. However, real ES for three or six weeks reversed these abnormal results; these parameters became similar to those of the NC rats and, consequently, voiding efficiency (VE) increased significantly from 17%–45% to 51%–57%. The cross-sectional area and axonal density of the pudendal nerve decreased in all the diabetic rats with sham ES for six weeks; however, these values increased significantly after real ES for six weeks. Significance. This study demonstrated the feasibility of using chronic pudendal neuromodulation for improving voiding function in diabetic rats. These results may facilitate the development of an advanced neural prosthesis for restoring bladder function in clinical settings.